2020
DOI: 10.1136/bmjopen-2019-035981
|View full text |Cite
|
Sign up to set email alerts
|

Using nutritional survey data to inform the design of sugar-sweetened beverage taxes in low-resource contexts: a cross-sectional analysis based on data from an adult Caribbean population

Abstract: ObjectiveSugar-sweetened beverage (SSB) taxes have been implemented widely. We aimed to use a pre-existing nutritional survey data to inform SSB tax design by assessing: (1) baseline consumption of SSBs and SSB-derived free sugars, (2) the percentage of SSB-derived free sugars that would be covered by a tax and (3) the extent to which a tax would differentiate between high-sugar SSBs and low-sugar SSBs. We evaluated these three considerations using pre-existing nutritional survey data in a developing economy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For the PAHO SSB tax survey, sugar-sweetened carbonated drinks and fruit drinks – with less than 100% fruit concentration – were selected as they represent the two SSB categories with the highest market share in volume sold in LAC (no data available for most Caribbean countries). 39 , 40 Energy drinks were also selected as volume sold has tripled in the last decade and they represent an emerging public health hazard, particularly for youths. 39 , 41 The fourth and last SSB category included was sugar-sweetened milk drinks as they may promote increased free sugar and energy intake and a previous analysis found that the majority of countries in LAC do not apply excise taxes on this SSB category.…”
Section: Methodsmentioning
confidence: 99%
“…For the PAHO SSB tax survey, sugar-sweetened carbonated drinks and fruit drinks – with less than 100% fruit concentration – were selected as they represent the two SSB categories with the highest market share in volume sold in LAC (no data available for most Caribbean countries). 39 , 40 Energy drinks were also selected as volume sold has tripled in the last decade and they represent an emerging public health hazard, particularly for youths. 39 , 41 The fourth and last SSB category included was sugar-sweetened milk drinks as they may promote increased free sugar and energy intake and a previous analysis found that the majority of countries in LAC do not apply excise taxes on this SSB category.…”
Section: Methodsmentioning
confidence: 99%
“…We identified the two most commonly consumed SSBs in the Barbados population: sodas and juice drinks ( Alvarado et al, 2020 ). We assessed the existence of an expressive risk signal around sodas and juice drinks separately, driven by the hypothesis that the risk signal produced by a tax may vary by product type.…”
Section: Methodsmentioning
confidence: 99%
“…The Minister of Finance cited high levels of diabetes and the need “to encourage healthier consumption patterns of our people as it relates to the consumption of sweetened beverages” as the rationale for the tax ( Sinckler, 2015 ). According to a nationally representative survey conducted between 2012 and 2013, adult SSB consumption was more than four times the global average ( Alvarado et al, 2020 ) and the prevalence of diabetes was double the global average ( Howitt et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%